The Effect of Multiwalled Carbon Nanotubes on the Thermal Conductivity and Cellular Size of Polyurethane Foam. (6th January 2021) - Duc, Huynh Mai; Huu, Dat Nguyen; Huu, Trung Tran; Trong, Lu Le; Nhu, Hai Luong; Ngoc, Hong Phan; Van, Thao Nguyen; Kieu Thi, Quynh Hoa; Vu, Giang Nguyen
Abstract : Polyurethane (PU) foam is known as the popular material for the applications in many fields of industry and life. To improve the mechanical and thermal properties of this material, in this research, PU foam was reinforced with aniline-modified multiwalled carbon nanotubes (MWCNTs). Fourier transform infrared FTIR spectrum of modified MWCNTs showed the aniline was grafted on the surface of MWCNTs through the appearance of –NH2 stretches. The effect of MWCNTs with and without modification on the density, porosity, compressive strength, and heat conductivity of PU/MWCNT foam nanocomposites was investigated. The dispersibility of MWCNTs in the PU matrix was enhanced after modification with aniline. Compressive strength of PU nanocomposite reached the highest value after adding 3 wt.% of modified MWCNTs into PU foam. Besides, the water uptake of PU nanocomposites using 3 wt.% of MWCNTs was decreased to 13.4% as compared to that using unmodified MWCNTs. The improvement in thermal conductivity of PU/aniline-modified MWCNT nanocomposite was observed due to the change in the cellular size of PU foam in the presence of MWCNTs as shown by SEM images.